DIPG-16. Evaluation of myeloid component of DIPG microenvironment. (3rd June 2022) - Mishra, Deepak; Rajendran, Sakthi; Zhu, Xiaoting; Nazzaro, Matthew; Kumar, Shiva Senthil; Mchugh, Todd; Rajappa, Prajwal; Drissi, Rachid
Abstract: Diffuse intrinsic pontine glioma (DIPG) is an aggressive and incurable disease of the central nervous system in children with median overall survival of less than one year. In recent years, several immunotherapy strategies have emerged as an option to treat DIPG. However, the low mutational burden and rare infiltration of T lymphocytes, render these tumors immunologically "cold" and therefore pose challenges for general immunotherapy. The myeloid component was implicated in the immunosuppression in other solid tumors. Previous data have shown that DIPG tumors are enriched in macrophages, but their role in tumor growth and progression have not been elucidated. Specifically, it remains unclear whether the myeloid cells are recruited to the tumor microenvironment from the peripheral circulation. Here, we examined the recruitment of myeloid cell populations to the tumor microenvironment and further delineated their role in tumor progression in a syngeneic mouse model of DIPG. We showed that this DIPG mouse model displays an immune microenvironment similar to that of patients' DIPGs. DIPG tumors harbored rare tumor infiltrating lymphocytes and are enriched in myeloid cells. To further characterize the phenotype and functions of these myeloid populations, we evaluated the changes in proportions of myeloid cell subsets using flow cytometry (CD11b, Ly6c, Ly6G, MHCII, F4/80, CD206, Arg1) in the bone marrow, peripheral blood, and in the tumor microenvironment during tumor progression. Also, we investigated the role of these myeloid cells in angiogenesis and immune suppression by performing histological and expression analyses of endothelial markers and chemokines (CD31, CD34, KDR, IL-10, IL-13, IL-4, CCL2, CCL5). Furthermore, decitabine (DNA methyltransferase inhibitor) treated tumors showed a decrease in myeloid population associated with a reduction in tumor growth, suggesting an important role of myeloid populations in tumor growth and progression.